Hubungan Beban Kerja dan Disiplin Kerja dengan Kinerja Pegawai di RSUD Nyi Ageng Serang Kulon Progo: The Relationship between Workload and Work Discipline with Employee Performance at Nyi Ageng Serang Kulon Progo Hospital - Rahmawati, Baiq Dwi Zulfa; Mudayana, Ahmad Ahid (International Journal of Healthcare Research, 2023)
Background: Healthcare workers contribute up to 80% to the improvement of well-being. The prioritization of healthcare human resources is crucial due to Indonesia still facing challenges in terms of workforce, encompassing quantity, types, quality, and distribution. The risks borne by healthcare personnel while working do not align with their workload, resulting in their unpreparedness when carrying out assigned tasks and responsibilities. RSUD Nyi Ageng Serang Kulon Progo is one of the hospitals where employees still bear dual responsibilities due to limited available resources. The use of manual attendance lists has not yet been able to provide accurate data regarding employee discipline. The purpose of this research is to determine the relationship between workload and work discipline with employee performance at RSUD Nyi Ageng Serang Kulon Progo. Results:  a Cross- Sectional research design with Chi-Square analysis. A total of 181 participants were selected as the research sample, chosen through the Stratified Random Sampling method. The instrument used is a questionnaire to measure workload, work discipline, and employee performance. Results: The research findings indicate a relationship between workload (p=0.000; OR=19.139), work discipline (p=0.000; OR=22.515), and employee performance at RSUD Nyi Ageng Serang Kulon Progo. Conclusion: There is a relationship between workload and work discipline with employee performance at RSUD Nyi Ageng Serang Kulon Progo.